Implementasi dan Dampak Media Promosi UMKM Marsalia Malang Melalui Pembuatan Video di Instagram Menggunakan Aplikasi Capcut - Salsabila Salsabila; Ahmad Fauzi (INDO PUBLISHING, 2026)
The development of information technology has encouraged businesses to utilize digital media as a promotional tool, including Instagram. Marsalia MSME has used Instagram for promotion; however, its promotional videos have not delivered product information effectively. This study aimed to develop promotional videos using the CapCut application for Instagram, evaluate their quality using the AIDA (Attention, Interest, Desire, Action) model, and analyze changes in the Engagement Rate by Reach (ERR) after publication. This study employed an action research approach based on the Kemmis and McTaggart model, consisting of the planning, acting, observing, and reflecting stages. Data were collected through observation, interviews, documentation, and questionnaires involving 10 respondents, consisting of the owner, employee, marketing experts, multimedia experts, and consumers. The results showed that the promotional video achieved effectiveness scores of 87.2% based on expert assessment and 93.3% based on public respondents' assessment, both categorized as excellent. All AIDA dimensions were rated as excellent, while the Engagement Rate by Reach increased from 3.13% to 7.7% after the video was published. These findings indicate that promotional videos developed using CapCut are effective as a digital promotional medium for Marsalia MSME. Future studies are recommended to apply similar promotional media on other digital platforms and employ additional effectiveness indicators.